THE SYMBOLIC MEANING OF THE ONCARAN TRADITION IN THE WEDDING CEREMONY OF THE PENDALUNGAN COMMUNITY - Hidayati, Febtri Darma; Sarofa, Faninatus; Mahbub, Mohahmmad Tarojjil; Anam, Asroful; Tjahyadi, Indra (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
This research focuses on the symbolic meaning of the Oncaran tradition contained in the marriage ceremony of the Pendalungan Probolinggo community. This research is important to do, because research on the local culture of the Pendalungan Probolinggo people is still minimal. The theory used as a theoretical basis in the analysis is the theory of George Herbert Mead's Symbolic Interactionism model. The method used in this study is descriptive qualitative method. The choice of this method is due to the purpose of this study which seeks to describe the symbolic meaning contained in the Oncaran tradition at wedding ceremonies in the Pendalungan Probolinggo community. Based on the research conducted, it was found that for the people of Pendalungan Probolinggo, the Oncaran tradition has meaning as 1) a symbol of hybrid identity, and 2) a symbol of brotherly values ​​in the Pendalungan Probolinggo community.